Cost identification analysis of general anesthesia - Rohit Malhotra; Nishant Kumar; Aruna Jain (Wolters Kluwer Medknow Publications, 2020)
Background and Aims : Rising health costs are challenging anesthesiologists to search for cost-effective anesthetic techniques. We conducted a study to estimate variable cost per case and cost of drug wastage as percentage of total drug cost associated with different modalities of general anesthesia (GA). Material and Methods: This prospective study was carried out after approval by institutional ethical committee in 258 adult patients aged 18-60 years of either sex, American Society of Anesthesiologists physical status I or II, with a surgical duration of 1-4 hours, posted for elective surgery under GA with endotracheal intubation. At the end of surgery, total utilization of each drug, anesthetic gases, and consumables were noted and remaining drug was regarded as wastage. Cost was recorded as per maximum retail price for that particular brand in the market at start of study and total cost was calculated. For purpose of analysis, cases were divided into low flow sevoflurane, high flow sevoflurane, high flow isoflurane, low flow isoflurane, and total intravenous anesthesia (TIVA). Results: The mean variable cost was highest with TIVA (₹2713.82 ± 509.57) and lowest with low flow isoflurane (₹1981.62 ± 335.03; P < 0.001). Drug wastage was 13.1% overall, with highest in low sevoflurane group and lowest in TIVA. Conclusion: Low flow anesthesia with isoflurane is more cost-effective as compared to high flow techniques and TIVA even for short duration surgeries. Rational use of drugs and consumables and minimizing wastage can further reduce anesthesia costs.